Comparison of cytokine profile of IFN-γ, IL-5 and IL-10 in cutaneous leishmaniasis using PBMC vs. whole blood - Mohammadi, Akram Miramin (Iran J Microbiol, 2019)
BACKGROUND AND OBJECTIVES: The surrogate marker (s) of cure and protection in intracellular pathogens is not yet well defined. The aim of this study was to compare the cytokine profile using whole blood cells (WBC) vs. peripheral blood mononuclear cells (PBMC) in healthy and cutaneous leishmaniasis (CL) volunteers. MATERIALS AND METHODS: In this study, WBC and PBMC of the volunteers with history of CL (HCL), Active lesion (ACL) and healthy volunteers were collected. The WBC and PBMC were cultured and stimulated with either PHA or soluble Leishmania antigens (SLA), after 72 hours, the supernatants were collected and the levels of IFN-γ, IL-5 and IL-10 were titrated using ELISA method. RESULTS: The mean ± SD of cytokines using WBC and PBMC in cutaneous leishmaniasis volunteers stimulated with phytohemagglutin (PHA) or SLA are as follow, PHA, IFN-γ=2295±995 vs. 2339±1115, IL-10=853±309 vs. 1330±966, and IL-5=299±136 vs. 352+156, SLA, IFN-γ, 931±824 vs. 825±532, IL-10, 233±78 vs. 408±381, and IL-5, 185±59 vs. 217±76, respectively. There was no significant difference between the IFN-γ, IL-5 and IL-10 levels using WBC vs. PBMC. There was a strong correlation between the cytokine profiles using WBC and PBMC in cutaneous leishmaniasis volunteers. CONCLUSION: There was no significant difference between IFN-γ, IL-10, IL-5 levels in whole blood and PBMC of volunteers with active lesion or history of CL. Whole-blood culture which is easier, cheaper and more convenient could be used instead of PBMC to evaluate the cytokine profile in field conditions.